2022
DOI: 10.1002/ajs4.253
|View full text |Cite
|
Sign up to set email alerts
|

Counting homelessness: Working creatively to generate complex descriptive profiles of the health and demographics of people experiencing homelessness in Adelaide

Abstract: Analyses of the prevalence of homelessness suggest homelessness is increasing in Australia and other countries. Yet, difficulties exist in obtaining an accurate picture of homelessness due to a dearth of robust data and inconsistent definitions. This study aimed to build a comprehensive descriptive profile of homelessness and associated health needs in Adelaide. Five data sources were analysed and compared to produce descriptive sociodemographic and health statistics. Across data sources, people experiencing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 37 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…Many of our research findings, including themes discussing the importance of effective communication, strong intersectoral partnerships built on trust, availability and coverage of services, adequate funding and having a shared vision and approach were consistent with findings across a range of different contexts (36,37,(39)(40)(41)(42)(43)(44). This demonstrates alignment with Kuruvilla et al 's (46) findings, which found similarities in how sectors collaborated between different research contexts.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Many of our research findings, including themes discussing the importance of effective communication, strong intersectoral partnerships built on trust, availability and coverage of services, adequate funding and having a shared vision and approach were consistent with findings across a range of different contexts (36,37,(39)(40)(41)(42)(43)(44). This demonstrates alignment with Kuruvilla et al 's (46) findings, which found similarities in how sectors collaborated between different research contexts.…”
Section: Discussionsupporting
confidence: 87%
“…Mutual trust and respect, fair decision-making processes, clear and effective communication and effective leadership were found to characterize successful intersectoral relationships ( 39 ). These factors promoting intersectoral collaboration have been replicated in recent literature, with common themes around access to resources, communication, trust, shared vision, decision-making equality, and structured and integrated modes of collaborating ( 36 , 37 , 39–44 ). Other studies have emphasized external influences that can have an impact on intersectoral collaboration, including the importance of sustainable financing and having access to secure, long-term and comprehensive financial means to sustaining intersectoral partnerships ( 45 ).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations